Exercise influence on the microbiome–gut–brain axis. (3rd September 2019) - Dalton, Alyssa; Mermier, Christine; Zuhl, Micah
ABSTRACT: The microbiome in the gut is a diverse environment, housing the majority of our bacterial microbes. This microecosystem has a symbiotic relationship with the surrounding multicellular organism, and a balance and diversity of specific phyla of bacteria support general health. When gut bacteria diversity diminishes, there are systemic consequences, such as gastrointestinal and psychological distress. This pathway of communication is known as the microbiome–gut–brain axis. Interventions such as probiotic supplementation that influence microbiome also improve both gut and brain disorders. Recent evidence suggests that aerobic exercise improves the diversity and abundance of genera from the Firmcutes phylum, which may be the link between the positive effects of exercise on the gut and brain. The purpose of this review is to explain the complex communication pathway of the microbiome–gut–brain axis and further examine the role of exercise on influencing this communication highway.